2016
DOI: 10.1111/jfpp.12846
|View full text |Cite
|
Sign up to set email alerts
|

Hot Air Drying Induces Browning and Enhances Phenolic Content and Antioxidant Capacity in Mung Bean (Vigna radiataL.) Sprouts

Abstract: Hot air drying has been widely used for the processing and preservation of fresh fruits and vegetables. In this study, we investigated the browning of hot air dried mung bean (Vigna radiata L.) sprouts, as well as the antioxidant capacity and phenolic contents in their soluble and insoluble fractions. Hot air drying at 70 and 80C for 24 h increased the browning of mung bean sprouts, and hot air dried samples generally had higher total phenolic content and antioxidant capacity compared to the freeze‐dried sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 27 publications
(33 reference statements)
1
18
0
4
Order By: Relevance
“…In alfalfa and flax sprouts, freeze-drying minimized the chemical alteration of the product, resulting in a better preservation of antioxidants and an increase in phytosterol availability [173]. Conversely, air drying at 70 and 80 • C for 24 h, as opposed to freeze drying (below −50 • C and 0.3 mbar vacuum pressure, 36 h), increased total phenolic content and antioxidant capacity of mung bean sprouts [174]. Pan-roasting of cereal (barley, wheat) sprouts was shown a promising heat processing for tea production, based on higher total phenolics and flavonoid contents and antioxidative effects in-vitro compared to a steaming process [169].…”
Section: Post-harvest Shelf Life and Processingmentioning
confidence: 99%
“…In alfalfa and flax sprouts, freeze-drying minimized the chemical alteration of the product, resulting in a better preservation of antioxidants and an increase in phytosterol availability [173]. Conversely, air drying at 70 and 80 • C for 24 h, as opposed to freeze drying (below −50 • C and 0.3 mbar vacuum pressure, 36 h), increased total phenolic content and antioxidant capacity of mung bean sprouts [174]. Pan-roasting of cereal (barley, wheat) sprouts was shown a promising heat processing for tea production, based on higher total phenolics and flavonoid contents and antioxidative effects in-vitro compared to a steaming process [169].…”
Section: Post-harvest Shelf Life and Processingmentioning
confidence: 99%
“…The effect of thermal exposure on bioactive compounds has been investigated in a number of plant species and most of these have indicated a degradation of alkaloids on exposure to heat and an enhancement of phenols [ 15 , 18 , 42 – 44 ]. Enhancement of phenolic compounds has been associated with thermal destruction of cell walls and subcellular compartments that results in increased levels of free phenolic compounds, the formation of novel compounds or the inactivation of deteriorative enzymes such as polyphenol oxidases [ 15 ].…”
Section: Main Textmentioning
confidence: 99%
“…However, the increase appeared to be concentrated the antioxidants during drying. Similarly, Gan, Lui, Chan, and Corke () observed that hot air‐drying incresaed the phenolic content and antioxidant capacity of mung bean sprouts. In general, there was an important reduction in total phenolic content of both varieties, except the samples dried for 10 hr, when fruits were dried.…”
Section: Resultsmentioning
confidence: 82%